Different corpus callosum in panic disorder - Kasikci, Halim Omer; Baykara, Sema; Balci, Hale Nur; Baykara, Murat (Elsevier Ireland Ltd, 2025)
Background: Despite hypotheses regarding the neurobiology of panic disorder (PD), its neurobiological basis is still unknown. Study results support that the individual differences in corpus callosum (CC) properties could reflect trait based alterations that predispose individuals to higher anxiety sensitivity, and to disorders associated with stress such as PD. Neuroimaging studies with panic disorder have not been sufficient to explain the pathophysiology of the disease. The aim of this study is to provide additional information for studies examining the etiology of PD by comparing the corpus callosum, a region associated with attention, anxiety, and somatic complaints, on sagittal MRI images of PD patients with the corpus callosum of healthy individuals. Methods: T2-weighted MRI images of 164 patients diagnosed with PD and 78 controls selected from Hospital Information System (HIS) and meeting the study criteria were evaluated by shape analysis method. Results: There were differences between the shapes and areas of the CC in the mid-sagittal images of the PD patients and healthy controls. Conclusions: This study findings highlighted the variable dimensional and subregional properties of CC in PD patients. This study could shed light on future studies about PD etiology, diagnosis and treatment.
Keywords: Computer-assisted image processing; Corpus callosum; Magnetic resonance imaging; Panic disorder